Mast cell degranulation by a hemolytic lipid toxin decreases GBS colonization and infection - Gendrin, Claire (Sci Adv, 2015)
Ascending infection of microbes from the lower genital tract into the amniotic cavity increases the risk of preterm birth, stillbirth, and newborn infections. Host defenses that are critical for preventing ascending microbial infection are not completely understood. Group B Streptococcus (GBS) are Gram-positive bacteria that frequently colonize the lower genital tract of healthy women but cause severe infections during pregnancy, leading to preterm birth, stillbirth, or early-onset newborn infections. We recently described that the GBS pigment is hemolytic, and increased pigment expression promotes GBS penetration of human placenta. Here, we show that the GBS hemolytic pigment/lipid toxin and hyperpigmented GBS strains induce mast cell degranulation, leading to the release of preformed and proinflammatory mediators. Mast cell–deficient mice exhibit enhanced bacterial burden, decreased neutrophil mobilization, and decreased immune responses during systemic GBS infection. In a vaginal colonization model, hyperpigmented GBS strains showed increased persistence in mast cell–deficient mice compared to mast cell–proficient mice. Consistent with these observations, fewer rectovaginal GBS isolates from women in their third trimester of pregnancy were hyperpigmented/hyperhemolytic. Our work represents the first example of a bacterial hemolytic lipid that induces mast cell degranulation and emphasizes the role of mast cells in limiting genital colonization by hyperpigmented GBS.